Internalizing Mental Health Disorders and Emotion Regulation: A Comparative and Mediational Study of Older Adults With and Without a History of Complex Trauma Exposure - Pfluger, Viviane; Rohner, Shauna L.; Eising, Carla M.; Maercker, Andreas; Thoma, Myriam V. (Frontiers in Psychology, 2022)
Individuals with complex trauma exposure (CTE) in early life (i.e., childhood/adolescence) are at heightened risk for developing problems in various domains of functioning. As such, CTE has repeatedly been linked to internalizing mental health disorders, such as depression and anxiety, as well as emotion dysregulation across the lifespan. While these correlates of CTE are comparatively well studied up to middle adulthood, they are insufficiently studied in older adulthood. Therefore, this study aimed to (a) compare Swiss older adults with and without a CTE history regarding current and lifetime internalizing mental health disorders and emotion regulation strategies; and (b) to examine the potential mediating role of emotion regulation in the mental health disparities between these groups. A total of N = 257 participants (age = 49-95 years; 46.3% female) were assessed in a retrospective, cross-sectional study, using two face-to-face interviews. The CTE group (n = 161; Mage = 69.66 years, 48.4% female) presented with significantly more current and lifetime internalizing mental health disorders than the non-affected (nCTE) group (n = 96; Mage = 72.49 years, 42.7% female). The CTE group showed significantly higher emotion suppression and lower emotion reappraisal compared to the nCTE group. Mediation analysis revealed that the two emotion regulation strategies were significant mediators between CTE history and internalizing mental health disorders. Findings emphasize the relevance of emotion (dys-)regulation in understanding mental health disparities in older age and deciding about treatment strategies. Research and practice should pay more attention to the needs of this high-risk group of older individuals.